Hubungan Pengetahuan dan Karakteristik Perawat dengan Kepatuhan Pelaksanaan Standar Operasional Prosedur Perawatan Luka - Nitinegari, Martha Megawati; Negoro, M. Syamsul Arif Setyo; Supriyadi, Supriyadi; Supadi, Supadi; Fitriyani, Aris (JURNAL KEPERAWATAN MERSI, 2025)
Background: Wound care is one of the techniques that nurses must master. The main principle in wound care management is infection control because infection inhibits the wound healing process, causing morbidity and mortality rates to increase. In carrying out wound care, nurses need to maintain the safety of patients and themselves with applicable Standard Operating Procedures (SOPs). Nurse compliance in implementing standard operating procedures is one measure of the success of wound care services. Objective: To know the relationship between the level of knowledge and compliance in the implementation of wound care according to SOP. Methods: The study was a correlational design and was conducted at RSUD K.R.M.T Wongsonegoro Semarang. The samples were 51 subjects collected by purposive sampling technique for surgical ward nurses. The data were analyzed by Spearman rank. Results: The results state that there is a relationship between the level of knowledge and the compliance of wound care SOP (p=0.000), gender and the compliance of wound care SOP (p=0.000), age and the compliance of wound care SOP (p=0.000), education and the compliance of wound care SOP (p=0.000), working length and the compliance of wound care SOP (p=0.000), and training and the compliance of wound care SOP (p=0.000). Conclusion: There is a relationship between the knowledge and characteristics of nurses (gender, age, level of education, length of work, and training) and compliance with the implementation of wound care according to SOPs.